Effect of representative designs on visual search behaviours in a table-tennis serving task among skilled players - Sim, Zena Kai Xin (2015)
Many studies has been done exploring the visual search (VS) patterns between expert and novice players and the quiet eye (QE) has emerged as a characteristic of higher levels of performance. The purpose of this study aims to explore the VS patterns of skilled table tennis players prior to serving. 4 expert table tennis players with 12 (±1) years of competitive experience performed 15 trials of serve in 2 conditions; with presence of a live receiver and absence of a live receiver. Measurements of performance outcome, QE duration and percentage of fixation was recorded. Despite only fixating the final gaze on the ball regardless of conditions, participant’s QE duration was significantly longer (M = 359.34ms vs 233.33ms, SE = 40.46ms vs 53.18ms) when a live receiver was present. The results imply that expert table tennis players require less attentional resources when they are required to perform a serve and a longer QE can help to maintain a better performance.